A produção de alimentos básicos: reestruturação regional? - Hoefle, Scott William (Anuário do Instituto de Geociências, 1994)
The evolution of development policy and the behavior of farm prices is related to change in the production of the traditional staples beans, manioc, maize and rice during three distinct periods: 1940-1964, 1964-1979 and 1979 to date. From 1940 onward staple production in the economic heartland of Brazil came under increasing pressure from expanding export and agroindustrial production on one hand and from discriminatory pricing policy on the other. In response to this pressure staple farmers in the South, Southeast and more recently in the Central-West increased productivity through flexible capitalization. Production continued to expand in these regions so that they still dominate the national market for beans, maize and rice. At the same time horizontal expansion of food production on the distant frontier proved to be insignificant and fell drastically in the depressed peripheral Northeast region disproving theses which attribute staple production to pre-capitalist peasant farmers of these regions.